Nasz Głos . dwutygodnik NSZZ "Solidarność" Ziemia Olkuska : [dwutygodnik Komisji Koordynacyjnej NSZZ "Solidarność" Ziemia Olkuska], no. 4, 1981 - [ed. committee] (NSZZ "Solidarność", 1981)
Creation and circulation: For organizational use